Association Between Serum Cortisol Levels, Stress Physiology, Pathological Changes, and Flare Frequency in Chronic Acne severity - Zarka Sarwar, Umair Farukh, Summeira Jabeen Shah, Sundas Shabir, Rahat Jan Wazir, Abdul Samad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic acne is a common inflammatory skin disease which can be due to hormonal, physiological, psychological and pathological factors. A rise in serum cortisol levels, from stress, can alter sebaceous gland activity, inflammation, and acne flare frequency. The correlation of serum cortisol levels with stress physiology, pathological changes and chronic acne severity still needs to be further assessed clinically. Objective: To determine the association between serum cortisol levels, stress physiology, pathological changes, and flare frequency with chronic acne severity. Methods: The study was descriptive cross-sectional study which was done at Mardan Medical Complex, Mardan from January 2023 to June 2023. A total of 75 patients with chronic acne was included. A structured proforma was completed for demographic data, duration of acne, family history, severity of acne, type of lesions, scarring, post-inflammatory hyperpigmentation, sleep disturbance, perceived stress level, and monthly frequency of flares. The acne was graded as mild, moderate or severe with clinical examination. Venous blood was drawn to measure cortisol in the morning. Data were analysed by employing SPSS. For quantitative variables, mean and standard deviation were used and for qualitative variables, frequency and percentage were used. Where appropriate, the following statistical analysis techniques were used: chi-square test, ANOVA, correlation analysis, and logistic regression. The p value was calculated and a value of < 0.05 was deemed statistically significant. Results: The mean age of the participants was 22.8 ± 4.9 years. Among 75 patients, 29 (38.7%) were males and 46 (61.3%) were females. Mild acne was observed in 21 (28.0%) patients, moderate acne in 34 (45.3%), and severe acne in 20 (26.7%). The mean serum cortisol level increased with acne severity, from 14.8 ± 3.7 µg/dL in mild acne to 19.3 ± 5.1 µg/dL in moderate acne and 25.1 ± 5.8 µg/dL in severe acne (p < 0.001). High perceived stress and frequent flare episodes were significantly more common among patients with severe acne. Serum cortisol level showed a positive correlation with acne severity score (r = 0.61, p < 0.001) and monthly flare frequency (r = 0.54, p < 0.001). Raised cortisol, high perceived stress, and frequent flares were significant predictors of moderate-to-severe acne. Conclusion: Higher serum cortisol levels, increased perceived stress, disturbed sleep, and frequent flare episodes were associated with greater chronic acne severity. Patients with severe acne showed more pathological changes, including scarring, post-inflammatory hyperpigmentation, and nodulocystic lesions. Assessment of stress physiology and flare frequency may be useful in the routine clinical evaluation of patients with chronic acne. Keywords: Acne vulgaris, serum cortisol, stress physiology, chronic acne, acne severity, flare frequency, pathological changes